2008
DOI: 10.1007/s11629-008-0098-8
|View full text |Cite
|
Sign up to set email alerts
|

Community tourism as practiced in the mountainous Qiang region of Sichuan Province, China — a case study in Zhenghe Village

Abstract: In China, community tourism is still a relatively new phenomenon, but the villagers of a small Qiang village in the Qiang Autonomous County of Beichuan in Southwestern Sichuan have initiated tourism in a way which conforms to the basic theory of community tourism development. This demonstrates that community tourism possesses a strength and vitality that can promote the development of tourism in the rural and mountainous areas. In the district of Zhenghe Village, the tourism industry, based on the community to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These webs shape the relative attractiveness and competitiveness of rural spaces economically, socially, culturally and environmentally (Murdoch 2000;Marsden 2010). Actors are essential and decisive factor in rural development (Lakshmanan 1982;Terluin 2003;Binns and Nel 2003;Phuthego and Chanda 2004;Zhou and Liu 2008), and thus it must be kept in mind that the perspectives of these (2009) and author's survey) Notes: Left, people of rural China and Shuanghe; right, out-migration and left-behind people of Shuanghe. The percentage of registered population that is of working age (customarily ages 15-64) in Shuanghe is 74.25%, a little higher than that in rural China (70.81%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These webs shape the relative attractiveness and competitiveness of rural spaces economically, socially, culturally and environmentally (Murdoch 2000;Marsden 2010). Actors are essential and decisive factor in rural development (Lakshmanan 1982;Terluin 2003;Binns and Nel 2003;Phuthego and Chanda 2004;Zhou and Liu 2008), and thus it must be kept in mind that the perspectives of these (2009) and author's survey) Notes: Left, people of rural China and Shuanghe; right, out-migration and left-behind people of Shuanghe. The percentage of registered population that is of working age (customarily ages 15-64) in Shuanghe is 74.25%, a little higher than that in rural China (70.81%).…”
Section: Discussionmentioning
confidence: 99%
“…Binns and Nel 2003;Zhou and Liu 2008). However, Jiang's (2007) survey showed that most of the village cadres were incapable to promote village development.…”
Section: Discussionmentioning
confidence: 99%
“…Social impacts usually raise concerns for residents, and include negative impacts such as prostitution (Sharma and Dyer, 2009), security and crime (Brida et al, 2011), overcrowding and traffic congestion (Kim, 2002) and spending habits of tourists that cause residents to resent their conditions (Mason, 2016). Positive social impacts relate to tourism development, including improvements to residents' quality of life (Zhou and Liu, 2008), increasing entertainment variety (Kim, 2002;Kim et al, 2013) and improvements to a destination's image (Stylidis et al, 2014). Pappas (2008) suggests that social impacts are affected by gender; men are more favorable to positive social impacts, and women are more concerned with negative social impacts.…”
Section: Social Impactsmentioning
confidence: 99%
“…So that it can spur people to maintain and preserve their cultural heritage [17]. Various opportunities can be maximized in the development of cultural villages, the diversity of historical tourist attractions in cultural towns can create historical tourist attractions that are adapted to the times.…”
Section: Cultural Village As a Potential Historical Tourist Attractionmentioning
confidence: 99%